2006
DOI: 10.1159/000091930
|View full text |Cite
|
Sign up to set email alerts
|

Detection of B chromosomes in interphase hemolymph nuclei from living specimens of the grasshopper <i>Eyprepocnemis plorans</i>

Abstract: The two most important evolutionary properties of B chromosomes are their transmission rate (which suggests their selfishness when significantly higher than 0.5) and their net effects on carrier fitness (usually negative for parasitic Bs). The study of transmission rate unavoidably requires the analysis of many controlled crosses in order to accurately measure population average transmission rate. Therefore, getting a marker closely associated to B presence is of crucial importance to alleviate the load of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…To date, B chromosome presence in E. plorans could only be determined by cytogenetic techniques, usually requiring animal sacrifice, since they are based on gonad analysis. The introduction of testis biopsy analysis (Ló pez-Leó n et al 1993b) permitted determining B chromosome presence in living males, and the development of a technique for determining B chromosome presence in interphase nuclei of hemocytes permitted analyzing B presence even in living females (Cabrero et al 2006). A PCR test for B-specific SCAR marker is applicable to live, dead, and preserved collection specimens.…”
Section: Discussionmentioning
confidence: 99%
“…To date, B chromosome presence in E. plorans could only be determined by cytogenetic techniques, usually requiring animal sacrifice, since they are based on gonad analysis. The introduction of testis biopsy analysis (Ló pez-Leó n et al 1993b) permitted determining B chromosome presence in living males, and the development of a technique for determining B chromosome presence in interphase nuclei of hemocytes permitted analyzing B presence even in living females (Cabrero et al 2006). A PCR test for B-specific SCAR marker is applicable to live, dead, and preserved collection specimens.…”
Section: Discussionmentioning
confidence: 99%
“…2 c). In a previous study in the E. plorans grasshopper, Cabrero et al [2006] suggested that the hemolymph is the best material to analyze living grasshoppers for the presence of B chromosomes using C-banding and fluorochrome staining. Here, we demonstrate that this type of cell is also useful for FISH experiments, allowing a reliable identification of the B chromosome and scoring the number of B chromosomes per nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Each animal was numbered and maintained in plastic boxes until the experiments were performed. A drop of hemolymph was obtained from the pleura of the thorax in the base of the third pair of legs using a needle [Cabrero et al, 2006]. The hemolymph was aspirated using a pipette and spread onto a clean slide.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations